The effect of acute slow resistance exercise on post-exercise blood pressure in active normotensive male recreational athlete - Ali Ramezanı; Naser Heıdarı (Türk Spor ve Egzersiz Dergisi)
Physical activity is a non-pharmacological way to prevent or treat disorders like type 2-diabete, obesity and hypertension. The aim of this study was to investigate The Effect of Acute Slow Resistance exercise on post-exercise blood pressure in active normotensive male recreational athlete. For this, Twelve recreationally active men were recruited, Brachial systolic blood pressure (SBP) and diastolic blood pressure (DBP) and heart rate were measured Immediately before (pre) and after(post) and approximately15 min(post-15), 30 min (post-30) and 60 min (post-60) after each exercise bout. Three resistance exercise bouts were performed: a high-intensity bout (HI), a low-intensity bout (LI) and a slow low-intensity (SL) resistance exercise bout. In each bout, 6 whole body exercises including: leg press, knee flexion, knee extension, bench press, lat pull down and biceps curl were performed. The SPANOVA test with repeated measures was used to analyze data. Our results showed that Significant time effect for SBP, DBP, MAP and HR (P lt;0.05). High intensity bout caused more stimulation for HR and HI and SL bout caused PHE (post-exercise hypotension) for DBP and MBP similarly greater than LI bout (P lt;0.05).  In our study all exercise bouts promote systolic and diastolic PEH in active normotensive subjects, while HI and SL exercise decreases DBP more than LI. perhaps Because SL method could promote PEH as much as HI method, although exercise intensity was lower in SL, it is recommended for people with special disabilities those who want to control hypertension with low exercise intensity and volume.